2010
DOI: 10.1155/2010/286925
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting Ovarian Cancer Metastatic Colonization: Insights from Metastasis Suppressor Studies

Abstract: Ovarian cancer affects approximately 25,000 women in the United States each year and remains one of the most lethal female malignancies. A standard approach to therapy is surgical cytoreduction, after which the remaining microscopic residual disease is treated with chemotherapy. The vast majority of patients have disease recurrence, underscoring the crucial need for approaches to control the regrowth, or colonization, of tissues after local treatment. Improved therapies require mechanistic information about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Our data demonstrate that placing pericytes in the tumor stroma of OVCAR-5 and -8 ovarian cancer cells while leaving the tumor vasculature intact results in accelerated tumor expansion via increased cell proliferation, shortening the latency of OVCAR-8 tumors by 15 days. Moreover, pericytes induced invasion and metastatic spread in nonmetastatic OVCAR-8 cells-a core clinical feature of aggressive serous ovarian cancer (1,44,45), and faster, distal spread of OVCAR-5 cells compared with controls that metastasized only locally within the peritoneal cavity to the gastrointestinal tract. These data demonstrate that normal MSC-like pericytes placed in close proximity to ovarian cancer cells drive malignant conversion, while normal fibroblasts do not affect tumor growth or metastasis, as reported previously.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our data demonstrate that placing pericytes in the tumor stroma of OVCAR-5 and -8 ovarian cancer cells while leaving the tumor vasculature intact results in accelerated tumor expansion via increased cell proliferation, shortening the latency of OVCAR-8 tumors by 15 days. Moreover, pericytes induced invasion and metastatic spread in nonmetastatic OVCAR-8 cells-a core clinical feature of aggressive serous ovarian cancer (1,44,45), and faster, distal spread of OVCAR-5 cells compared with controls that metastasized only locally within the peritoneal cavity to the gastrointestinal tract. These data demonstrate that normal MSC-like pericytes placed in close proximity to ovarian cancer cells drive malignant conversion, while normal fibroblasts do not affect tumor growth or metastasis, as reported previously.…”
Section: Discussionmentioning
confidence: 97%
“…Statistics from the United States (NCI) and United Kingdom (CRUK)-countries with some of the highest rates of ovarian cancer-show that although diagnosis at stage 1 at a young age is associated with approximately 90% survival, the overwhelming majority of patients with ovarian cancer ($85%) are diagnosed at advanced stages of disease (3 and 4), after metastatic dissemination (1). Despite aggressive surgical intervention combined with chemotherapeutic and platinum/paclitaxel treatment to eliminate residual cancer, 60% to 70% of late-stage ovarian cancer patients relapse with recurrence, dying within 2 years of treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EOC is a leading cause of death from gynaecological malignancy (Jemal et al, 2007). Ovarian cancer metastases are frequently established by a unique microenvironmental niche comprised of tumour and inflammatory cells, along with a wide range of bioactive soluble factors, including ET-1 (Khan et al, 2010;Barbolina et al, 2009;Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and experimental studies have identified the final step of ovarian cancer progression, metastatic colonisation of peritoneum, as a tractable therapeutic target (Barbolina et al, 2009;Khan et al, 2010). Molecular characterisation of ovarian cancer has led to the identification of potential molecular targets for new treatments, including ET A R. Since the results of the clinical trials of zibotentan as a monotherapy and in combination with cytotoxic drugs to interrupt the ET-axis has met with mixed levels of success, in which the promising delay in disease progression did not translate into an overallsurvival benefit (Bagnato et al, 2011), the discovery of new biologic co-targeted agents is an exciting new chapter in the treatment of gynecologic malignancies.…”
Section: Discussionmentioning
confidence: 99%